Jemparingan as Cultural Heritage and Character Education: Philosophical Values and Preservation Strategies in Contemporary Society - Subaryana, Subaryana; Fibiona, Indra; Lestari, Siska Nurazizah (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
Jemparingan, the traditional seated archery of the Ngayogyakarta Hadiningrat Sultanate, represents a unique cultural heritage that integrates physical practice with spiritual self-development. Addressing the need for character education in the digital age, this study investigates how Jemparingan fosters essential focus and discipline within Generation Z. Utilizing a historical and anthropological approach, the research analyzes the sport’s historical evolution from a royal-exclusive tradition to a modern cultural practice, while examining its philosophical emphasis on the unity of mind and body. The study further evaluates current preservation challenges and identifies key policy efforts necessary to sustain this tradition. Results indicate that the sport’s distinct cross-legged technique demands acute concentration and fine motor control, serving as an effective pedagogical tool for instilling self-regulation. The paper concludes that integrating Jemparingan into modern educational frameworks offers a strategic avenue for cultural continuity and for supporting the psychological development of contemporary adolescents.